Letramento de resistência : o que as paredes das ruas de Itapuranga (GO) têm a dizer? - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The aim of this research is to analyze graffiti as literacy events, in order to understand what graffiti-subjects seek to express in this specific inner city context, in order to understand their social realities and if they (not) resist harsh patterns of social exclusion. So, because it is an investigation of the motivating social problems, it is a qualitative interpretative research, and it seeks to read the graffiti, with all the meanings that may be intrinsic between the paint and the wall. Intersubjectivity is a strong factor in this process, because the understanding of meanings (CELANI, 2005) will lead us to a possible journey of communication with graffiti subjects. Twenty graffiti were collected in the city of Itapuranga (GO) for analysis and identification of resistance literacy from graffiti. The main references that led to understand how to capture and read the object of study were Duarte(2002); Souza(2009); Mittmann (2012); Padilla (2013); Sito (2016); Araújo (2017), which enabled a feasible methodological understanding for a study that seeks discourses and literacies from a narrative that goes beyond hegemonic writing in Brazil, writing from printed or digital space. Therefore, resistance Literacy can be considered a social event, in which the subjects use writing through graffiti in Itapuranga (GO), highlighting their contexts, disputes, conflicts in which the records were produced, evidencing in this case these practices such as literacy events. In this way, resistance is perceived and articulated through graffiti, producing socially situated literacies. It was also possible to identify local literacies of social reading of the piches starting from the cultural context of the researched city. From the analysis it becomes clear that voices of resistance echo in a town in the countryside of Goiás, they are located, put the sights of the local community, conquering their voice space. Therefore, the research contributes to the reflection of the significant amplitude of the literacy studies, supported by the studies of Street (2007), that defends the literacy that represents the most diverse uses and meanings of reading and writing in the most diverse social, cultural and different epochs.
Resistance literacy : what do the walls of the streets of Itapuranga(GO) have to say?
Keywords: Picho - Itapuranga(GO) - Letramento de resistência; Picho - Letramento de resistência; Graffiti - Itapuranga(GO) - Resistence literacy; Graffiti - Resistence literacy; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA